A social-ecological network approach for understanding wildfire risk governance. (January 2019) - Hamilton, Matthew; Fischer, Alexandra Paige; Ager, Alan
Highlights: We assess social-ecological alignment in a wildfire risk governance system. To measure alignment, we couple a governance and a wildfire transmission network. We define risk interdependence archetypes which provide opportunities for alignment. Three archetypes facilitate social-ecological alignment. One archetype highlights the limits of self-organizing governance networks. Abstract: Large wildfire events (e.g. >100 square km) highlight the importance of governance systems that address wildfire risk at landscape scales and among multiple land owners and institutions. A growing body of empirical work demonstrates that environmental governance outcomes depend upon how well patterns of interaction among actors align with patterns of ecological connectivity, such as wildfire transmission. However, the factors that facilitate or inhibit this alignment remain poorly understood. It is crucial to improve understanding of the conditions under which actors establish or maintain linkages with other actors with whom they are interdependent because of ecological linkages. To this end, we introduce the concept of "risk interdependence archetypes" based on the spatial configurations by which one actor (i.e. a particular organization) is exposed to risk via the actions of another actor. We then develop a set of hypotheses to explore how different sets of conditions associated with each spatial configurations of risk interdependence may shape the likelihood that an actor coordinates with another actor in ways that promote social-ecological alignment. We test these hypotheses using network analysis of a wildfire transmission network developed through simulation of wildfires over several thousand fire seasons and a governance network created from interviews with 154 representatives of 87 organizations involved in efforts to mitigate wildfire risk in the Eastern Cascades Ecoregion, USA. Results indicate that social-ecological alignment is more likely when actors have opportunities to influence forest management practices on ignition-prone lands that they do not manage themselves, and when actors bear greater responsibility for averting losses from wildfires that spread to lands they manage independently. Importantly, not all forms of risk interdependence increase the likelihood of alignment, implying that organizations have limited capacity for interaction and may prioritize certain risk mitigation partnerships over others. While the performance of risk governance systems may hinge on the alignment of social and ecological networks, our results suggest that alignment in turn may depend on actor-level strategies for interaction with other actors.